Development and validation of the Multidimensional Gender Inequality Perception Scale (MuGIPS). - Sofía Schwartz-Salazar; Efraín García-Sánchez; Rocío Martínez; Rosa Rodríguez-Bailón (PLoS ONE, 2024)
Perceptions of gender inequality may motivate people to take action against inequality given its negative impact on various domains of people's everyday lives. Thus, it is crucial to develop reliable measures that consider the multidimensional nature of gender inequalities. In this research, we propose and assess the psychometric properties of the Multidimensional Gender Inequality Perception Scale (MuGIPS). This is a self-reported measure of perceived gender inequality in four domains: health, violence, household work and caregiving, and public sphere and power. Exploratory and confirmatory factor analyses were conducted to test the validity and reliability of the MuGIPS with Spanish participants in three samples (N = 1733). The analyses revealed that the MuGIPS had a good internal consistency and showed four factors associated with gender inequality in the four specified domains. Moreover, scores in all the dimensions positively correlated with feminist identity and feminist ideology, as much as with some attitudinal variables. In contrast, results showed a negative correlation with system-justifying ideologies. The MuGIPS shows adequate reliability and validity for measuring the perception of gender inequality in the health, violence, household work and caregiving, and public sphere and power domains among Spanish university and general population samples.